I am an artist - Slade-Robinson, Nikki 1968- (Duck Creek Press, 2016)
A young girl describes how she can make art anywhere, with anything
Picture story book for children
Keywords: Art / Juvenile fiction; Nature (Aesthetics) / Juvenile fiction; Art / Fiction; Nature (Aesthetics) / Fiction; Art; Nature (Aesthetics); Picture books; Picture books for children; Children's stories, New Zealand; Children's picture books; Fiction; Juvenile works; Bilderbuch